What’s in a translation rule? - Galley, Michel; Hopkins, Mark; Knight, Kevin; Marcu, Daniel (Proc. of HLT-NAACL, 2004)
We propose a theory that gives formal semantics to word-level alignments defined over parallel corpora. We use our theory to introduce a linear algorithm that can be used to derive from word-aligned, parallel corpora the minimal set of syntactically motivated transformation rules that explain human translation data.